The Peculiarity of the Compound Sentences in the Text of the Religious- polemical Works Written by Belarusian-Polish-Lithuanian Tatars - Kozhinowa, Alla (Slavistica Vilnensis, 2019)
The present paper focuses upon syntactic peculiarities of an arabographic text by Belarusian-Lithuanian-Polish Tatars. The text is extracted from manuscript P97 which dates back to the 18th century and is now stored at the Central Scientific Library of the Belarusian Academy of Sciences. The object of our study is a compound sentence. The paper concludes that the text under analysis, abundant in bookish constructions, displays no competition between literary Polish of that period, its regional variant and the East Slavic languages at the level of syntax, i.e. in terms of compound sentences.
Keywords: Belarusian-Lithuanian-Polish Tatars; Polish language; Belarusian language; sentence